2020
DOI: 10.1063/5.0013165
|View full text |Cite
|
Sign up to set email alerts
|

Inertial dynamics of an interface with interfacial mass flux: Stability and flow fields’ structure, inertial stabilization mechanism, degeneracy of Landau’s solution, effect of energy fluctuations, and chemistry-induced instabilities

Abstract: This work focuses on the interfacial dynamics with interfacial mass flux in the presence of acceleration and surface tension. We employ the general matrix method to find the fundamental solutions for the linearized boundary value problem conserving mass, momentum and energy. We find that the dynamics can be stable or unstable depending on the values of the acceleration, the surface tension and the density ratio. In the stable regime, the flow has the non-perturbed fields in the bulk, is shear-free at the inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(49 citation statements)
references
References 81 publications
1
48
0
Order By: Relevance
“…The mixing-layer thickness variations would imply non-ideal flow modifications to the pictures described in the shock refraction problem, altering the local properties at the tangential discontinuities and introducing a characteristic length scale. Moreover, a detailed study of interfacial transport and mixing within the multi-species reacting shear layer that may be subject to multiple shocks interactions, transport of species and radiation, calls for multi-scale modelization coupling kinetic to meso-and macroscopic dynamics [59,60]. Nevertheless, the numerical analysis of complete turbulent, viscous and diffusive flows is out of the scope of this work, which serves to a prior understanding of the thermallyperfect considerations in shock refractions of high speed flows.…”
Section: Influences On the Mixing Layermentioning
confidence: 99%
“…The mixing-layer thickness variations would imply non-ideal flow modifications to the pictures described in the shock refraction problem, altering the local properties at the tangential discontinuities and introducing a characteristic length scale. Moreover, a detailed study of interfacial transport and mixing within the multi-species reacting shear layer that may be subject to multiple shocks interactions, transport of species and radiation, calls for multi-scale modelization coupling kinetic to meso-and macroscopic dynamics [59,60]. Nevertheless, the numerical analysis of complete turbulent, viscous and diffusive flows is out of the scope of this work, which serves to a prior understanding of the thermallyperfect considerations in shock refractions of high speed flows.…”
Section: Influences On the Mixing Layermentioning
confidence: 99%
“…Particularly, group theory approach grasped the order in Rayleigh-Taylor mixing and explained the observations [11,19,[21][22][23][24][25][26][27]. For interfaces with interfacial mass flux, a rigorous theory of the interface stability was developed recently for ideal fluids [17,[28][29][30]. This theory discovered the inertial mechanism of interface stabilization, the instability of the conservative dynamics of accelerated interface, and the chemistry-induced instabilities [17,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…For interfaces with interfacial mass flux, a rigorous theory of the interface stability was developed recently for ideal fluids [17,[28][29][30]. This theory discovered the inertial mechanism of interface stabilization, the instability of the conservative dynamics of accelerated interface, and the chemistry-induced instabilities [17,[28][29][30]. It also resolved the prospect of Landau 1944 and found that classical Landau's solution for Landau-Darrieus instability is a perfect mathematical match [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations